The influence of initial conditions on turbulent mixing due to Richtmyer-Meshkov instability - Thornber, Ben; Drikakis, Dimitris; Youngs, D. L.; Williams, R. J. R. (Cambridge University Press, 2010)
This paper investigates the influence of different three-dimensional multi-mode initial conditions on the rate of growth of a mixing layer initiated via a Richtmyer-Meshkov instability through a series of well-controlled numerical experiments. Results are presented for large-eddy simulation of narrowband and broadband perturbations at grid resolutions up to 3 x 10(9) points using two completely different numerical methods, and comparisons are made with theory and experiment. It is shown that the mixing-layer growth is strongly dependent on initial conditions, the narrowband case giving, a power-law exponent theta approximate to 0.26 at low Atwood and theta approximate to 0.3 at high Atwood numbers. The broadband case uses a perturbation power spectrum of the form P(k) proportional to k(-2) with a proposed theoretical growth rate of theta = 2/3. The numerical results confirm this; however, they highlight the necessity of a very fine grid to capture an appropriately broad range of initial scales. In addition, an analysis of the kinetic energy decay rates, fluctuating kinetic energy spectra, plane-averaged volume fraction profiles and mixing parameters is presented for each case.
Keywords: rayleigh-taylor instability large-eddy simulation high-resolution methods high- order homogeneous turbulence numerical-simulation compressible flows shock-wave acceleration driven